ACOMODAÇÃO SENSORIAL COMO RECURSO TERAPÊUTICO OCUPACIONAL NA PRÁTICA DA INTEGRAÇÃO SENSORIAL NO AUTISMO (REMUNOM, 2025)
The Sensory Integration Disorder affects more than 90% of the individuals with Autism Spectrum Disorder through hypersensitivity, hyposensitivity and discrimination deficits, which interfere with daily activities, cognition and socialization. This article aims to analyze the contributions of the study of Sensory Integration studies to clinical reasoning for recommending sensory accommodation within the autism spectrum. This is a study employs a qualitative approach, specifically a literature review. Documents were sourced online from the Google Scholar database, indexed journals such as Scielo, TOG, among others, and digital repositories of national universities over the last 10 years, using the following keywords: sensory diet, sensory accommodation, sensory integration. A total of 73 articles related to sensory integration were identified, with 19 published between 2014 and 2019, 28 between 2020 and 2022 and 26 between 2023 and 2024. Of these, only 19% addressed sensory diet. The production of knowledge in ​​sensory accommodation/diet is significant given the limited publications in the past 10 years.